2020
DOI: 10.4236/aim.2020.1010038
|View full text |Cite
|
Sign up to set email alerts
|

<i>Aflatoxin</i> M1 (<i>Aspergillus parasiticus, flavus</i>) Occurrences in Milk and Milk Products and Its Possible Health Effects

Abstract: Aflatoxin M1 (AFM1) occurrence in milk and milk products has been a major concern among food scientists over the past three decades owing to its possible health risk in humans. The well-documented AFM1 associated adverse health outcomes include hepatocarcinogens, mutagens genotoxins, mutagenicity, and teratogen. The paper reviews the occurrence of AFM1 in milk, milk products, and human milk in developing and developed countries, with its safety standards of regulation. The health associated risks with AFM1 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The presence of mold contamination not only degrades the quality of food and animal feed, but it can also have adverse effects on human health. The potential health risks associated with AFM1 exposure have been widely documented in previous studies [ 28 , 29 ]. High levels of AFM1 exposure were associated with an increased risk of liver cancer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of mold contamination not only degrades the quality of food and animal feed, but it can also have adverse effects on human health. The potential health risks associated with AFM1 exposure have been widely documented in previous studies [ 28 , 29 ]. High levels of AFM1 exposure were associated with an increased risk of liver cancer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has also documented the occurrence of AFM1 contamination in dairy products, including raw milk [ 28 ]. Our study was comparable to research performed by Busman et al [ 32 ] who stated that 24 out of 26 raw milk samples were contaminated with AFM1.…”
Section: Resultsmentioning
confidence: 99%
“…About 0.3% to 6.2% of AFB1 is converted to AFM1 and classified as a cause of human liver cancer. Excretion of AFM1 in milk can take 12 -24 hours after the ingestion of AFB1; however, there is a decrease in concentration after 72 hours (Fallah et al, 2011;Alahlah et al, 2020;Bukari et al, 2020). AFM1 is resistant to autoclaving, pasteurization, and thermal inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…However, when AFB1 is produced by fungi and when animals digest contaminated feed, their liver metabolizes the AFB1 into hydroxylated aflatoxin-AFM1 which, if the animal is milking, will be secreted out into milk. Milk and dairy products play a vital role in human daily meals, it is important to bring issues to light health risks to all actors who work in the dairy value chain (Serraiono et al 2019;Bukari et al 2020;Djekic et al 2020). AFs are classified by the International Agency for Research on Cancer (IARC) as Group 1 carcinogens to humans (IARC, 2009;Ismail et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…AFM1 can be carried out with the circulation system to the mammary glands and let down into milk (Min et al 2021). Bukari et al (2020), found that about 0.3 % -6.2 % of AFM1 can be excreted in milk if the cow is milking. Also, the prevalence of AFM1 in raw milk can be revealed 12-24 hours after ingestion and absorption of feed polluted with AFB1.…”
Section: Introductionmentioning
confidence: 99%